Pedagogical practices focused from neuroeducation (Memorias Sifored - Encuentros Educación UAN, 2021)
Generate and reflect among teachers and students about cognitive stimulation in the classroom and its effects on learning through the application of new pedagogical practices focused on neuroeducation and emotional education.
Keywords: neuroeducation; Emotional education; pedagogical practice